2011
DOI: 10.1186/cc10547
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in hospital-wide mortality after implementation of a rapid response team: a long-term cohort study

Abstract: IntroductionRapid response teams (RRTs) have been shown to reduce cardiopulmonary arrests outside the intensive care unit (ICU). Yet the utility of RRTs remains in question, as most large studies have failed to demonstrate a significant reduction in hospital-wide mortality after RRT implementation.MethodsA cohort design with historical controls was used to determine the effect on hospital-wide mortality of an RRT in which clinical judgment, in addition to vital-signs criteria, was widely promoted as a key trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 39 publications
1
93
2
1
Order By: Relevance
“…218 The other study demonstrated a significant difference between control wards and intervention wards (introduction of a critical care outreach service) with all patients (OR, 0.70; 95% CI, 0.50-0.97), and matched randomized patients (OR, 0.52; 95% CI, 0.32-0.85). 219 Of the 33 nonrandomized studies reporting mortality, no studies reported statistically significant worse outcomes for the intervention; 15 studies with no adjustment demonstrated no significant improvement [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] ; 6 studies with no adjustment demonstrated significant improvement [235][236][237][238][239][240] ; 1 study with no adjustment reported on rates, which improved with MET, but did not report on significance 241 ; 1 study with no adjustment demonstrated significant improvement for medical patients but not surgical patients (combined significance not reported) 242 ; 4 studies with adjustment demonstrated significant improvement both before and after adjustment 243,244,250,252 ; 2 studies with adjustment demonstrated no significant improvement both before and after adjustment 245,246 ; 2 studies with adjustment demonstrated significant improvement before adjustment but not after adjustment 247,251 ; 1 study with adjustment demonstrated significant improvement before adjustment but not after adjustment 27 ; 1 study that reported on both unexpected mortality and overall mortality showed significant improvement both before and after adjustment for unexpected mortality but no significant improvement both before and after adj...…”
Section: Consensus On Sciencementioning
confidence: 99%
“…218 The other study demonstrated a significant difference between control wards and intervention wards (introduction of a critical care outreach service) with all patients (OR, 0.70; 95% CI, 0.50-0.97), and matched randomized patients (OR, 0.52; 95% CI, 0.32-0.85). 219 Of the 33 nonrandomized studies reporting mortality, no studies reported statistically significant worse outcomes for the intervention; 15 studies with no adjustment demonstrated no significant improvement [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] ; 6 studies with no adjustment demonstrated significant improvement [235][236][237][238][239][240] ; 1 study with no adjustment reported on rates, which improved with MET, but did not report on significance 241 ; 1 study with no adjustment demonstrated significant improvement for medical patients but not surgical patients (combined significance not reported) 242 ; 4 studies with adjustment demonstrated significant improvement both before and after adjustment 243,244,250,252 ; 2 studies with adjustment demonstrated no significant improvement both before and after adjustment 245,246 ; 2 studies with adjustment demonstrated significant improvement before adjustment but not after adjustment 247,251 ; 1 study with adjustment demonstrated significant improvement before adjustment but not after adjustment 27 ; 1 study that reported on both unexpected mortality and overall mortality showed significant improvement both before and after adjustment for unexpected mortality but no significant improvement both before and after adj...…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Results of earlier studies in terms of hospital mortality were conflicting, with several studies [8,14], [17][18][19][20][21][22][23] showing a reduction and others [9,11,13,[24][25][26][27][28] showing no change or even an increase [29] in hospital mortality following rapid response system implementation. A systematic review and meta-analysis from Chan et al [11] did not demonstrate any overall benefit from rapid response systems in terms of hospital mortality (pooled RR = 0.96 [0.84-1.09]) with a significant heterogeneity of results (I 2 = 90.3%; p < 0.001).…”
Section: Hospital Mortalitymentioning
confidence: 95%
“…Only a few studies [8,11,14,20,24,30,31] limited the analysis to cardiac arrests outside the ICU and none of these studies conducted any blinded outcome assessment. Almost all studies on rapid response systems have a before-and-after design, which makes them prone to bias.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…33 In addition to vital signs criteria, judgment that prompt assistance was needed at the bedside was emphasized to staff as an important criterion for RRT activation by Beitler and colleagues. 40 As a result, they reported significant reductions in hospital-wide mortality, out-of-ICU mortality, and out-of-ICU cardiopulmonary arrests. 40 Although outcomes vary from study to study, the beneficial effects of RRTs are becoming clearer as the intervention is more universally applied.…”
Section: Impact Of Rrts On Patients' Outcomesmentioning
confidence: 99%
“…40 As a result, they reported significant reductions in hospital-wide mortality, out-of-ICU mortality, and out-of-ICU cardiopulmonary arrests. 40 Although outcomes vary from study to study, the beneficial effects of RRTs are becoming clearer as the intervention is more universally applied. Benefit has been reported in many hospital settings using a variety of RRS models even though this has not firmly translated into a consistent reduction in overall hospital mortality.…”
Section: Impact Of Rrts On Patients' Outcomesmentioning
confidence: 99%